Brilliance of the moon - Hearn, Lian. (London : MacMillan Children's Books, 2005)
Takeo, secretly wed to his beloved Kaede, sets out to help her reclaim her lands and avenge the deaths of his biological and adoptive fathers, all the while aware of the prophecy that he must fight five battles--four to win, and one to lose.
Adult.
Adult
Keywords: Inheritance and succession -- Fiction; Married people -- Fiction; Revenge -- Fiction; Adventure fiction; Historical fiction; Inheritance and succession -- Fiction; Married people -- Fiction; Revenge -- Fiction; Japan -- Fiction; Japan -- Fiction; Adventure fiction; Historical fiction